Igniting Climate Entrepreneurship in Morocco : Findings from the Climate Entrepreneurship and Innovation Ecosystem Diagnostic - World Bank Group (World Bank, Washington, D.C., 2017)
Climate-smart development is a rapidly growing area in Morocco, and indeed much of the world. It has simultaneously been proven to boost economic development and contribute to more sustainable economic development by reducing emissions and energy costs, creating jobs, and increasing economic opportunity. A World Bank Group (WBG) team, together with the support of Cluster Solaire’s and the Moroccan Agency for Sustainable Energy (MASEN), undertook a climate entrepreneurship ecosystem diagnostic in Morocco. The purpose was to shed light on the complexities of the country’s climate entrepreneurship ecosystem. The overarching aim of this report is to inform different ecosystem stakeholders in Morocco on how to spur and sustain high-growth, green entrepreneurship and innovation activity. At the same, this report also aims to increase the awareness of and support to green entrepreneurs, as well as contribute substantively to the design of the aforementioned International Finance Corporation (IFC)-supported activity.